Struktur Cerita Rakyat Kunun Puti Bensu Model Vladimir Propp - Pebwike Sari; Irma Suryani; Sovia Wulandari (Kajian Linguistik dan Sastra, 2023)
Abstract This study aims to describe the functions of actors in 3 versions of the Kunun Puti Bensu folklore. The approach used in analyzing the functions of actors is based on the structure theory of Vladimir Propp's folklore which contains 31 functions of actors. The research results obtained in analyzing the functions of the perpetrators of the 3 versions of the Kunun Puti Bensu folklore based on the folklore structure theory of Vladimir Propp's model were the discovery of 20 of the 31 functions of the actors, including (Î²) a family member leaving the house, (Î³) a prohibition uttered to the main character, (Î´)Prohibition is broken, (Îµ)The robber tries to spy, (Î¶)The robber receives a report about his enemy, (Å‹)The robber tries to deceive his prey in order to own it or possess his possessions, (Î¸)The prey is deceived and unknowingly helps his enemies, (Ð)The robber causes trouble for a family, (Ð°) A family feels deprived and wants to have something, (Î’)An accident or shortage is announced, the main character is asked or ordered, he is allowed to go or sent, (C )The seeker agrees or decides to take revenge, (â†‘)The main character leaves the house, (F)The main character gets a powerful agent, (G)U character first delivered, given directions to the destination or object sought, (J)The main character is injured, (I)The robber is defeated, (K)The initial accident or shortage is resolved, (â†“)The main character goes home, (Rs)The main character is saved, (W) The main character gets married and ascends the throne. Â Abstrak Penelitian ini bertujuan untuk mendeskripsikan fungsi pelaku yang terdapat pada 3 versi cerita rakyat Kunun Puti Bensu. Adapun pendekan yang digunakan dalam menganalisis fungsi pelaku adalah berdasarkan teori struktur cerita rakyat Vladimir Propp yang memuat 31 fungsi pelaku. Hasil penelitian yang diperoleh dalam menganalisis fungsi pelaku terhadap 3 versi cerita rakyat Kunun Puti Bensu berdasarkan teori struktur cerita rakyat model Vladimir Propp adalah ditemukannya sebanyak 20 fungsi pelaku dari 31 fungsi pelaku antara lain (Î²)Seorang anggota keluarga meninggalkan rumah, (Î³)Suatu larangan diucapkan kepada tokoh utama, (Î´)Larangan dilanggar, (Îµ)Perampok mencoba untuk memata-matai, (Î¶)Perampok menerima laporan tentang musuhnya, (Å‹)Perampok mencoba memperdaya mangsanya dengan tujuan untuk memilikinya atau memiliki kepunyaannya, (Î¸)Mangsanya terpedaya dan tanpa disadari membantu musuhnya, (Ð)Perampok menyebabkan kesusahan seorang keluarga, (Ð°) Seorang keluarga merasa kekurangan dan ingin memiliki sesuatu, (Î’)Kecelakaan atau kekurangan diumumkan, tokoh utama diminta atau diperintahkan, ia dibenarkan pergi atau di utuskan, (C)Pencari setuju atau memutuskan untuk membalas dendam, (â†‘)Tokoh utama meninggalkan rumah, (F)Tokoh utama memperoleh agen sakti, (G)Tokoh utama diantar, diberi petunjuk menuju ke tempat tujuan atau objek yang dicari, (J)Tokoh utama terluka, (I)Perampok dikalahkan, (K)Kecelakaan atau kekurangan awal diatasi, (â†“)Tokoh utama pulang, (Rs)Tokoh utama diselamatkan, (W)Tokoh utama menikah dan menaiki tahta.